Income Exploration and Behavioral Bias in Insurance Customers’ Decision-Making: A Qualitative Study at PT Asuransi BDIR - Bayu Irawan; Sitti Rakhman (Paspama Institute, 2025)
This study aims to explore the influence of income levels on behavioral bias tendencies among insurance customers in their decision-making at PT Asuransi BDIR. A qualitative approach with a case study method was employed to gain an in-depth understanding of how biases such as loss aversion, overconfidence, availability bias, and status quo bias emerge in decisions to purchase, retain, or cancel insurance policies. The informants included customers from three income categories (low, middle, and high), as well as two insurance agents and one customer service staff for source triangulation. Data collection techniques involved in-depth interviews, non-participant observation, and documentation, analyzed through thematic analysis. The findings indicate that income moderates the presence of certain behavioral biases. Low-income customers tend to exhibit defensive biases such as loss aversion and availability bias, while high-income customers are more prone to overconfidence and mental accounting. These findings highlight the need for tailored communication and education approaches based on customer behavioral characteristics. The study recommends implementing behavior-based education strategies, behavioral coaching training for agents, and psychographic segmentation to enhance communication effectiveness and policy retention.